2020
DOI: 10.1080/07418825.2020.1849360
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinion on Support for Arming Teachers with Guns in the United States

Abstract: Proposals to arm teachers with guns have emerged in reaction to high-profile school shootings in the United States. Though controversial, these proposals have gained the support of various policymakers and special-interest groups. Public opinion, however, is largely divided on the issue and split on political lines. This study seeks to unpack the reasons why Americans may support arming teachers, drawing from multiple theoretical perspectives. Findings indicate support for the culture conflict perspective, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Similar to previous polls, those holding rightward political views are more supportive of arming teaching and nonteaching staff (Baranauskas, 2020;Bonn, 2019;Mancini et al, 2020;Morning Consult/Politico, 2018;NBC News/SurveyMonkey, 2018). Notably, NRA members are more likely to support the controversial measure of specifically bringing guns into the classroom by arming teachers.…”
Section: Political Valuessupporting
confidence: 52%
See 1 more Smart Citation
“…Similar to previous polls, those holding rightward political views are more supportive of arming teaching and nonteaching staff (Baranauskas, 2020;Bonn, 2019;Mancini et al, 2020;Morning Consult/Politico, 2018;NBC News/SurveyMonkey, 2018). Notably, NRA members are more likely to support the controversial measure of specifically bringing guns into the classroom by arming teachers.…”
Section: Political Valuessupporting
confidence: 52%
“…In contrast to much consensus about arming SROs, cleavages are revealed when examining support for arming teachers and nonteaching staff. The respondents split approximately 40% for and 40% against arming school personnel, with a substantial minority (20%) undecided on the issue (see also Baranauskas, 2020). Given this division, the policy debate over arming the schoolhouse is likely to remain contentious for the foreseeable future (Baranauskas, 2020;Bonn, 2019;Mancini, Cook, Smith, & McDougle, 2020;Morning Consult/Politico, 2018;NBC News/SurveyMonkey, 2018;Parker, Horowitz, Igielnik, Oliphant, & Brown, 2017).…”
Section: Divided Support For Arming Teachers and Staffmentioning
confidence: 99%
“…MHI opinions about honor, standing up in a fight, and using violence as a response to threats are not specific to White men from the South. These considerations may inform policy and intervention decisions especially when gun (Baranauskas, 2021; Shepperd et al, 2018) and police violence (Pomerantz et al, 2021) permeate public health and policy discussions. These considerations are especially pertinent as MHI and gun enthusiasm predict lifetime aggression (Matson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The push to arm teachers has sparked an intense amount of debate. Americans are largely divided in support for arming teachers along political lines, with conservative Americans being more likely to support arming teachers (Baranauskas, 2020; Horowitz, 2018).…”
mentioning
confidence: 99%
“…Recent research has also found that support for arming teachers is largely divided into racial lines, with African Americans being significantly less likely to support policies that aim to arm teachers with guns (Baranauskas, 2020; Shamserad et al, 2020). This makes sense given greater patterns in attitudes toward crime and justice among people of color, namely that African Americans are more likely to be distrustful of the police and the criminal justice system (see Brunson, 2007; Sharp & Johnson, 2009; Tyler, 2005) and less supportive of punitive measures to address crime (Unnever & Cullen, 2010).…”
mentioning
confidence: 99%